The Role of SMEs in International Trade: Selected Aspects - Joanna Malecka (Institute of Economic Research (IER), 2017)
Research background: International trade is an important stimulant for economic development that simultaneously ensures free access to raw materials, goods, services and technologies. It essentially involves trade in goods, yet what is also significant is the invisible trading sphere (tourism, transport, financing sources). Being a vital factor in macro-economic policies pursued by contemporary national economies, SMEs build the single market, which integrates the European economy, through trade development that directly fosters economic growth. Purpose of the article: The article strives to answer the question whether EU-based SMEs enjoy benefits and greater stability as well as state support when operating in foreign markets. The article presents the contribution of SMEs to international trade conducted by selected EU countries and Poland. The results of the author's own research relate to the share of SMEs in the sectoral and geographical structure. Methodology/methods: The research findings are based on source data from annual reports and publications that have been produced and made available by financial market institutions and on the author's own research concerning Polish entrepreneurs. The volume and structure of SME imports and exports in the various markets are outlined by means of analyses, figures and comparisons. Findings: The author's own research shows that Polish entrepreneurs operating in international markets are primarily driven by: (1) profitability of transactions, (2) prospects for establishing long-term cooperation, and (3) high demand for products originating in their country in foreign markets. The ongoing standardisation and unification with respect to internationalisation should be supported by the state along with forms of financial security and contract insurance. What SMEs expect most is support as regards co-financing investments that are a necessary and costly element of the international activity development process.
Keywords: F02; F43; F63; L11; L26; 330; export; import; SME; international trade; internationalisation